2021
DOI: 10.3390/ani11020520
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Electrolyte Balances during Periovulatory Period in Cycling Mares

Abstract: In cycling females, the periovulatory period is characterized by stimulation of the hypothalamic pituitary adrenal (HPA) axis. The aim of present study was to analyze the pattern and interrelationships among adrenocorticotropic hormone (ACTH), cortisol (CORT), aldosterone (ALD) and electrolytes (sodium—Na+, potassium—K+ and chloride—Cl−) during periovulatory period in cycling mares. Venous blood samples were obtained daily from a total of 23 Purebred Spanish broodmares, aged 7.09 ± 2.5 years, from day −5 to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…There is a correlation between sodium, potassium, and chloride levels and progesterone levels, as well as between estradiol and Cl − . According to Satué et al (2021) [54], ovarian steroid hormones influence the excretion of mares. At the highest concentration of estrogen, loss of Na + is observed, while at the beginning of the luteal phase in sheep, sodium reabsorption is observed, which is associated with the secretion of progesterone and aldosterone.…”
Section: Electrolytes In the Female Reproductive Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a correlation between sodium, potassium, and chloride levels and progesterone levels, as well as between estradiol and Cl − . According to Satué et al (2021) [54], ovarian steroid hormones influence the excretion of mares. At the highest concentration of estrogen, loss of Na + is observed, while at the beginning of the luteal phase in sheep, sodium reabsorption is observed, which is associated with the secretion of progesterone and aldosterone.…”
Section: Electrolytes In the Female Reproductive Systemmentioning
confidence: 99%
“…A correlation of Cl − with progesterone concentrations has also been demonstrated in mares and women [ 54 ]. In the research conducted by Satué et al (2021) [ 54 ] in healthy mares aged about seven years, it was shown that the highest concentration of sodium and chloride were recorded during ovulation (day zero) compared to the pre- and post-ovulation period. The concentration of Na + was 142.2 ± 3.28 nmol/L and for Cl − : 107.4 ± 1.44 nmol/L.…”
Section: Electrolyte Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the HPG axis has been shown to have a significant impact on adrenal function in a variety of mammalian species. Adrenal cortisol release increases during estrous behaviour and/or ovulation in domestic species [34,35] and humans [36] and seasonal reproductive activity has been shown to be associated with an increase in adrenal cortisol output in koalas [37] and monkeys [26]. Given that 55% of the FCM observations during the breeding season of February to April were associated with temperatures ≤5 • C, the interaction of breeding season on temperature-associated changes in FCM concentrations is not surprising (Figure 4).…”
Section: Sub-analyses Of Sexually Mature Adult Polar Bearsmentioning
confidence: 98%